La población estudiantil en el sétimo año de la educación pública costarricense - Alfaro Rodríguez, Magdalena (2009)
Seventh grade students share personal characteristics that are analyzed in this paper based on the teachers´ performance of the proper mediation for the students´ learning. The results of an investigation done with the model of teachers´ profiles at this level will be the basis for this paper (Alfaro et al, 2008a). We conclude that the biopsychosocial development and maturational stage of the transit-preteen-teen children must be the domain of faculty at this level, as well as, the socioeconomic context of family and social contexts of their students.